2012
DOI: 10.1590/s1676-26492012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Screening symptoms of depression and suicidal ideation in people with epilepsy using the Beck depression inventory

Abstract: Objective: To measure the severity of symptoms of depression and suicidal ideation in people with epilepsy (PWE) before and after epilepsy surgery using the Beck Depression Inventory (BDI). We aimed to determine the factors associated to depression in PWE. Methods: PWE, regardless of epilepsy type, seizure type, duration or frequency of seizures, and AEDs were investigated. The sample (n=468) was divided into two groups: preoperatory (n=346) and pos-operatory (n=122). Results: Before epilepsy surgery female ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
2
0
2
Order By: Relevance
“…Regarding suicidal attempt, the current study found that the prevalence of lifetime suicidal attempt among people with epilepsy was 14.1% which is closely consistent with many other reports in Egypt (11.5%) [ 12 ], Croatia (14.6%) [ 25 ], and Brazil (12.1%) [ 26 ]. However, this result was higher than the study done in Bosnia and Herzegovina (18%) [ 22 ], Cuba Havana (28.6%) [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding suicidal attempt, the current study found that the prevalence of lifetime suicidal attempt among people with epilepsy was 14.1% which is closely consistent with many other reports in Egypt (11.5%) [ 12 ], Croatia (14.6%) [ 25 ], and Brazil (12.1%) [ 26 ]. However, this result was higher than the study done in Bosnia and Herzegovina (18%) [ 22 ], Cuba Havana (28.6%) [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Considering the low prevalence of suicidal ideation, the expected frequency is rather small, wherefore separate Fisher‐Freeman‐Halton exact tests were used (Fisher, ). “Suicidal ideation” was specified as values at or above 1, on the suicidal ideation‐item of BDI‐FS, and “no suicidal ideation” as scores of zero (Casey et al, ; Green et al, ; Salgado et al, ). As there are no prior investigations on PTS and stress on suicidal ideation, we cannot apply a priori effect sizes to calculate a minimum sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Although most people who have suicidal ideation do not commit suicide, it is reported as an important indicator for patients at risk (Brown, Beck, Steer, & Grisham, 2000). The BDI suicide item has been used as a screening tool for suicide in previous research with the cutoff of 1 being conspicuous (Casey et al, 2006;Salgado, Nogueira, Yasuda, & Cendes, 2012) and was shown to have predictive (Green et al, 2015;Wenzel et al, 2011) and convergent validity (Desseilles et al, 2012).…”
Section: Suicidal Ideationmentioning
confidence: 99%
“…A epilepsia é uma patologia associada a várias consequências para o indivíduo, sejam elas no âmbito médico, psicológico, econômico ou social. Dentre as comorbidades psiquiátricas relacionadas a essa condição, a depressão é a mais prevalente (SALGADO et al, 2012). Essa relação é descrita desde os tempos antigos, quando Hipócrates afirmou que "os melancólicos normalmente se tornam epiléticos, e epiléticos, melancólicos; o que determina a preferência é a direção que a doença toma; se incide sobre o corpo, epilepsia, se sobre a inteligência, melancolia" (VALENTE; BUSATTO FILHO, 2013).…”
Section: Aspectos Geraisunclassified
“…Com relação as atividades ocupacionais, observa-se que o desemprego é duas a quatro vezes maior nos pacientes epilépticos do que na população em geral, o que decorre, entre outros fatores, do preconceito por parte de empregadores e da dificuldade de adaptação. Isso contribui de forma significativa para o desenvolvimento da depressão, principalmente nos indivíduos desempregados de longa data, visto que o emprego traz implícito uma sensação de ajustamento social e valor perante a sociedade (SALGADO et al, 2012).…”
Section: Fatores Psicossociaisunclassified